KONSEP KEADILAN HUKUM (KONSEP BARAT, KONSEP ISLAM, DAN KONSEP PANCASILA) - Muhammad Samsuri (MAMBA'UL 'ULUM, 2018)
Justice, since the first issue, has been the subject of study both thinkers, among philosophers, legal experts, politicians or among theologians. However, if there are questions about justice, could not be determined what measures are used to determine something is fair or not. Various answers about justice usually never or rarely satisfying so that continues to be debated, so it canbe concluded that the various formulations of justice is a relative statement. This issue ultimately encourages many people to take a shortcut by submitting formulation of justice to the legislators and judges who will formulate it based on their own considerations.